2007
DOI: 10.1016/j.bbrc.2007.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Mutations that alter the equilibrium between open and closed conformations of Escherichia coli maltose-binding protein impede its ability to enhance the solubility of passenger proteins

Abstract: Certain highly soluble proteins, such as Escherichia coli maltose-binding protein (MBP), have the ability to enhance the solubility of their fusion partners, making them attractive vehicles for the production of recombinant proteins, yet the mechanism of solubility enhancement remains poorly understood. Here, we report that the solubility-enhancing properties of MBP are dramatically affected by amino acid substitutions that alter the equilibrium between its "open" and "closed" conformations. Our findings indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…At times, for purification purposes, MBP-fusion protein does not bind to the amylose-affinity resin. Other times, after release from the affinity resin, protein precipitates out, possibly because the protein is misfolded or prone to aggregation in its native state [7, 10]. Here we show that another carbohydrate-binding protein, human galectin-1, can be an efficient fusion partner.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…At times, for purification purposes, MBP-fusion protein does not bind to the amylose-affinity resin. Other times, after release from the affinity resin, protein precipitates out, possibly because the protein is misfolded or prone to aggregation in its native state [7, 10]. Here we show that another carbohydrate-binding protein, human galectin-1, can be an efficient fusion partner.…”
Section: Introductionmentioning
confidence: 80%
“…The best studied and most thoroughly validated solubility-enhancing protein is the maltose-binding protein (MBP). Structural studies of MBP have shown that it is an efficient enhancer of solubility only in the open conformation of the carbohydrate recognition domain (CRD) [10]. It is most likely that the CRD of the maltose binding protein is involved in folding of the passenger protein.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that MBP inhibits the formation of insoluble aggregates by transiently binding folding intermediates of an aggregation-prone passenger protein, effectively sequestering it in an intramolecular interaction that impedes the kinetically competing pathway of intermolecular aggregation and precipitation [4]. A corollary of this hypothesis is that MBP must be folded before it can bind to and sequester its passenger protein [6, 9]. If so, then as a result of co-translational folding, it follows that MBP should function as a more effective solubilizing agent when it is fused to the N-terminus of a passenger protein than to its C-terminus because in the former case MBP would emerge first from the ribosome and have time to fold before the passenger protein is translated.…”
mentioning
confidence: 99%
“…Several mechanisms have been proposed to explain how MBP can enhance the solubility of the fusion protein [31,32]. It seems reasonable to assume that MBP can keep the proteins that it fused with in a properly folded form.…”
Section: Stability Assaysmentioning
confidence: 99%